Human Milk Composition Differs by Maternal BMI in the First 9 Months Postpartum. (29th May 2020) - Sims, Clark; Lipsmeyer, Melissa; Turner, Donald; Andres, Aline
Abstract: Objectives: Recent studies indicate that human milk composition is modulated by maternal weight status; however, results are conflicting. The objective of this study was to examine the relationship between maternal body composition and human milk macronutrients and bioactive components, as well as the association between infant daily intakes and infant body composition. Methods: Human milk samples (N = 990) were obtained from a longitudinal study (NCT#0, 113, 1117) in normal weight (NW: 18.5–24.9 kg/m, 2 N = 88) and overweight/obese (OW: 25–35 kg/m, 2 N = 86) women between 0.5 and 9 months postpartum. Macronutrient content was estimated using mid-infrared spectroscopy (MIRIS AB). Leptin, insulin, C-reactive protein (CRP), IL-6, IL-8 and TNF-α were measured using electrochemiluminescence immunoassays (Meso Scale Diagnostics). Infant body composition was obtained using quantitative magnetic resonance (Echo-MRI-AH). Linear mixed models adjusted for postpartum age and infant sex. Results: Human milk was higher in fat and protein, and lower in carbohydrate content at only a few time points in OW compared to NW mothers. Human milk leptin and insulin concentrations were higher in OW mothers throughout lactation and CRP content differed at most time points compared to NW mothers. Similar results were observed when concentrations were normalized to infant daily intake and body weight. The effect sizes of infant daily intakes associated with infant growth parameters were small for macronutrients (0.005 to 0.05 Z-score units and 0.02 to 0.45 fat mass index (FMI)/fat free mass index (FFMI) units per unit of change in composition). Larger effect sizes were seen with human milk insulin and leptin, with infants of OW mothers exposed to 1.5 to 2.5 times higher concentrations compared to infants of NW mothers. Conclusions: This study allows for a more comprehensive understanding of maternal BMI effects on human milk composition and its association with infant growth. Of note, the concentrations of leptin and insulin in human milk from OW mothers were higher than those in milk from NW mothers, resulting in higher daily intakes by their infants and modulation of FMI from 0.5 to 9 months postpartum. This study demonstrates the value of considering both human milk composition and infant daily intake when assessing infant growth. Funding Sources: USDA/ARS Project # 6026–51, 000-012–06S, NIH R01 DK107516.